Plasma treatment in textile industry - Zille, Andrea (2015)
Plasma technology applied to textiles is a dry, environmentally- and worker-friendly method to achieve surface alteration without modifying the bulk properties of different materials. In particular, atmospheric non-thermal plasmas are suited because most textile materials are heat sensitive polymers and applicable in a continuous processes. In the last years plasma technology has become a very active, high growth research field, assuming a great importance among all available material surface modifications in textile industry. The main objective of this review is to provide a critical update on the current state of art relating plasma technologies applied to textile industry